Do Different Next-to-Skin Garments Change Thermal Sensation, Jump Height and Landing Knee Valgus After Cold Exposure? - Ben Kasehagen; Susan Morris; Kevin Netto (Applied Sciences)
Exposure to the cold can negatively affect muscle performance. This study compared the effects of two different full-length, lower body, next-to-skin garments on thermal sensation, countermovement jump (CMJ) height and knee frontal plane angle upon landing following cold exposure against a control. After familiarisation, 13 male and 11 female recreationally active adults attended three separate laboratory testing sessions where a randomly assigned next-to-skin garment was used (compression, thermal and control (shorts)). A pre- and post-testing protocol comprising CMJ and drop landings interspersed with a sedentary cooling period of 40 min at 0 °C was adopted. High-speed motion analysis and subjective ratings of thermal sensation were recorded. Exposure to the cold significantly reduced thermal sensation (p < 0.001) scores and CMJ height (p < 0.001). Only female participants felt significantly warmer (p ≤ 0.009) in the next-to-skin garments. Losses in CMJ height were significantly reduced by the next-to-skin garments compared to the control with the thermal garment producing better results. There was little change in knee frontal plane angle upon landing in all the garments tested. Ambient cooling at 0 °C for 40 min had a significant effect on CMJ height and thermal sensation but not knee valgus upon landing. Participants in winter sports should consider next-to-skin garments in conjunction with proper warm-ups and re-warming techniques to protect themselves from the negative effects of the cold.